2013
DOI: 10.1149/2.012305jss
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Polishing of Al-Co Films for Replacement Metal Gate Applications

Abstract: Further development of a novel cobalt-Al-based metal fill scheme that can be scaled to 11 nm requires the planarization of the metal overfill overburden while also protecting it from corrosion. Very recently, we showed that KMnO4 and sucrose-based aqueous solutions can reduce the ΔEcorr between Al and Co to ∼10 mV. The present work describes the development of the associated silica-based slurry compositions for polishing the Al-Co alloy films. The influence of dodecyl benzene sulfonic acid (DBSA) in tuning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The model is compared with the experimental data 52,53 and good agreement is obtained. Unless otherwise indicated, the specific values of the following parameters are set to be V = 0.5m/s, E p = 3M Pa, υ = 0.2, k 1 = 4.87×10 −6 m/s, M = 27g/mol and ρ 0 = 2.7g/cm 3 for convenience in the following simulation and verification.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The model is compared with the experimental data 52,53 and good agreement is obtained. Unless otherwise indicated, the specific values of the following parameters are set to be V = 0.5m/s, E p = 3M Pa, υ = 0.2, k 1 = 4.87×10 −6 m/s, M = 27g/mol and ρ 0 = 2.7g/cm 3 for convenience in the following simulation and verification.…”
Section: Resultsmentioning
confidence: 81%
“…In the present calculation, the concentration of oxidizer is 0.003 mol/L, the particle diameter is 35 nm and the slurry pH is 6 which is same as the experiment. 53 The Fig. 2 shows that the increase of the abrasive loading leads to the increase of the MRR.…”
Section: Resultsmentioning
confidence: 94%
“…It is found that KMnO 4 is a good oxidizer which can achieve oxidbillity preservation and be used to enable the formation of a protective MnO 2 film to reduce the corrosion potential gap and minimize galvanic corrosion. 8,9 According to the Pourbaix diagram of Al, 7 the oxide or hydroxide is not stable and can be dissolved into the slurry under the acidic environment and the rate constant k 32 :…”
Section: Modelingmentioning
confidence: 99%
“…In the alkaline region in the presence of KMnO4 four cathodic reactions, oxygen reduction (reaction 6) and the three permanganate ion (MnO 4 -reduction reactions (reaction7, 8 and 9) consume the electrons generated from the anodic reactions (1)(2)(3)(4)(5). It is well known that during the permanganate ion reduction, (MnO 4 -gets reduced to MnO2 and adsorbs on the surface of the metal films [7][8][9]. The MnO2 can in turn be reduced to Mn2O3 and MnOOH (reactions 8,9).…”
Section: Ru/tin As Barriermentioning
confidence: 99%
“…It is well known that during the permanganate ion reduction, (MnO 4 -gets reduced to MnO2 and adsorbs on the surface of the metal films [7][8][9]. The MnO2 can in turn be reduced to Mn2O3 and MnOOH (reactions 8,9). However, especially, in the KMnO4 oxidizer system, similar corrosion potential values of the three films Cu, Ru and TiN indicates that the MnO2, Mn2O3 and MnOOH formed on all the three surfaces could fill the porous regions as well as form an adsorbed passive layer on the respective oxides and hydroxides.…”
Section: Ru/tin As Barriermentioning
confidence: 99%